2020
DOI: 10.47909/ijsmc.02
|View full text |Cite
|
Sign up to set email alerts
|

Patents information for humanities research: Could there be something?

Abstract: Latour and co-authors proposed, in the Science and Technology Translation theory, to target the many SHS (Social and Human Science) questions addressed by social studies of sciences by considering, in complement to traditional academic matters, the complete social environment (political, economic or societal). Patents obviously are a potential primary information source to do so. We propose to extend this considering that recent changes have evolved in our capacity to do so. We propose three preliminary steps:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Furthermore, based on fieldwork, the results of [50][51][52][53] and [54][55][56][57][58] were corroborated, revealing the diversity of mobile phone usage by participants, even when not connected to the internet. Similarly, as in the work of [59][60][61][62][63][64], it was possible to find discrepancies between the perception of safe technology and social media use [65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, based on fieldwork, the results of [50][51][52][53] and [54][55][56][57][58] were corroborated, revealing the diversity of mobile phone usage by participants, even when not connected to the internet. Similarly, as in the work of [59][60][61][62][63][64], it was possible to find discrepancies between the perception of safe technology and social media use [65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 80%
“…The selection of the two main indicators (patents and innovations) for the identification of the sample of projects for the analysis may limit the representation of Social Sciences and Humanities (SSH) – related projects in the final selected sample. This can be considered as expected for two reasons: i) the generation of patents and similar innovation results are more likely to happen from Innovators that are industrial and/or commercial in their nature ( HRB report, 2023 ); and ii) the use and submission of patents and similar innovations, is traditionally reserved to domains of science and technology, like the STEM (Science, Technology, Engineering, Mathematics) and medicine/biomedicine/drugs disciplines ( HRB report, 2023 ; Reymond, 2020 ). However, relevant research has shown for example, that an in-depth analysis in patent sources can provide useful information on SSH topics beyond those of mere technological intelligence ( Reyomond, 2020 ).…”
Section: Methodsmentioning
confidence: 92%